Pengaruh Pola Asuh Orang Tua Terhadap Tingkat Kenalakan Remaja: Studi Kasus Remaja Kota Binjai, Jln. T. Imam Bonjol - Tanjung, Samsidar; Simatupang, Saharani Gibran; Ritonga, Maria; Hakim, Mohammad Lukmanul; Br Ginting, Icha Marta Friska; Mode, Aninda Nesya (Universitas Pahlawan Tuanku Tambusai, 2024)
This research was conducted based on the rampant behavior of juvenile delinquency to the detriment of others, especially in the neighborhood of Jl. T. Imam Bonjol, Binjai City. This is thought to be the impact of the covid-19 pandemic which makes students stay at home all day and feel bored, leading to behavior outside the values and norms of society. So that raises questions about parenting. This study uses a qualitative descriptive method in which data collection is carried out by means of direct observation and interviews with adolescents and parents in the observation environment. From this study, it produces a conclusion that explains that the level of juvenile delinquency at this time is caused by parenting patterns of parents who are indifferent to the behavior shown by their children.